The use of Arsenicum album 30c to complement conventional treatment of neonatal diarrhoea (‘scours’) in calves - Kayne, S.; Rafferty, A. (British Homeopathic Journal, 1994)
In a pilot double blind study carried out in Scotland, the effect of supplementing a conventional treatment plan with homoeopathic Arsenicum album was studied. In the management of neonatal calf scour it appeared that more animals recovered after one day in the group that had received active medicine, than in the placebo group. These results are encouraging.
Keywords: Scours; Arsenicum album; Calves; Diarrhoea; neonatal; Veterinary medicine